Element partitioning and electron backscatter diffraction analysis from feeding wire to as-deposited microstructure of wire and arc additive manufacturing with super duplex stainless steel - Zhang, Xiaoyong; Wang, Kehong; Zhou, Qi; Kong, Jian; Peng, Yong; Ding, Jialuo; Diao, Chenglei; Yang, Dongqing; Huang, Yong; Zhang, Tao; Williams, Stewart W. (Elsevier, 2019)
The redistribution of alloying elements and the crystallographic characterizations in wire and arc additive manufactured (WAAM) super duplex stainless steel (SDSS) was investigated from the wire to the final as-deposited structure. The results showed that elemental partitioning between austenite and ferrite was suppressed in the last layer and the solidified droplet. The high Ni content but low Cr and N contents in the initial state of the intragranular austenite (IGA) confirmed the predominance of the chromium nitrides acted as the nucleation sites. Gathering of nitrogen was found more distinct in the coarsening IGA, Widmanstätten austenite (WA) than the grain boundary austenite (GBA). The columnar epitaxial ferrite presented a strong <001> texture in the deposition direction, while the <001> and <101> orientations was found in the austenite. Random orientations of the intragranular secondary austenite was revealed. The Rotated Cube texture of the austenite grains were consumed by the “recrystallization” textures (Brass, Rotated Brass, Cu, R, E, and F) caused by the austenite reformation. The low-angle interphase boundaries between austenite and ferrite were predominated in the as-deposited wall, and, at which, the K–S orientation took the crucial part. A Taylor factor analysis revealed that through fabrication via additive process, the austenite became oriented “harder” and contributed most to good mechanical properties. The textured microstructure contributed about a 2.6% higher engineering strain in the Z direction and a 27.8 MPa higher yield strength in the X direction.
Keywords: Wire and arc additive manufacturing; Super duplex stainless steel; Element partitioning; Texture and phase boundary orientations; Taylor factor